2017
DOI: 10.1016/j.mrgentox.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cell transformation induced by synthetic amorphous silica nanoparticles

Abstract: International audienceSynthetic amorphous silica nanoparticles (SAS) are among the most widely produced and used nanomaterials, but little is known about their carcinogenic potential. This study aims to evaluate the ability of four different SAS, two precipitated, NM-200 and NM-201, and two pyrogenic, NM-202 and NM-203, to induce the transformation process. For this, we used the recently developed in vitro Bhas 42 cell transformation assay (CTA). The genome of the transgenic Bhas 42 cells contains several copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Recent works have, however, shown that cell transformation assays are useful tools to predict carcinogens [ 146 ]. In particular, the CTAs can be useful to identify non-genotoxic carcinogens and should be included as an integral part of a battery of in vitro tests in order to predict carcinogenic potential of chemicals and also NMs [ 147 ]. Fontana et al investigated four different amorphous non-genotoxic silica particles with the CTA and indicated one non-genotoxic carcinogenic out of two pyrogenic and two precipitated silica materials [ 147 ].…”
Section: Carcinogenicitymentioning
confidence: 99%
“…Recent works have, however, shown that cell transformation assays are useful tools to predict carcinogens [ 146 ]. In particular, the CTAs can be useful to identify non-genotoxic carcinogens and should be included as an integral part of a battery of in vitro tests in order to predict carcinogenic potential of chemicals and also NMs [ 147 ]. Fontana et al investigated four different amorphous non-genotoxic silica particles with the CTA and indicated one non-genotoxic carcinogenic out of two pyrogenic and two precipitated silica materials [ 147 ].…”
Section: Carcinogenicitymentioning
confidence: 99%
“…This decrease, observed at concentrations inducing a weak inhibition of cell proliferation at Day 7, is likely explained by a more pronounced inhibition of cell growth after 21 days of culture due to the three repeated treatments during the promotion assay. This phenomena was also observed with amorphous silica NMs [49] as well as with other non-carcinogenic chemicals such as Lascorbic acid and caffeine [68]. [24].…”
Section: Discussionmentioning
confidence: 54%
“…The CTA in promotion condition, originally proposed by the OECD [16], was modified as described previously [8] ( Supplementary Fig. A.1).…”
Section: Cell Transformation and Cell Survival Assaysmentioning
confidence: 99%
“…Two long-term carcinogenesis studies with SAS have been published to date, showing that repeated intratracheal instillations of pyrogenic SAS in rats increased the incidence of lung tumors [6,7]. Recently, we showed that precipitated and pyrogenic SAS (NM-200, NM-201 NM-202 and NM-203) induced the transformation of Bhas 42 cells in cell transformation assays (CTA) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation